AKSELERASI PEMAHAMAN MBKM DAN PELEMBAGAAN KEMITRAAN STRATEGIS DI SMA NEGERI 45 MALUKU TENGAH - Alfonsina Marthina Tapotubun; Natelda R. Timisela; Juliana B. Mamesah; Hellen Nanlohy; Fransina Latumahina; Mirtha Y. S. Risakotta; Revency V. Rugebregt; Imelda K. E. Savitri; Edison Jambormias; Jogenes Patty; R. B. D. Sormin (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
The implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy requires readiness not only from higher education institutions but also from secondary education units as strategic upstream partners. However, a significant literacy gap exists in coastal regions, particularly at SMA Negeri 45 Maluku Tengah. Despite the availability of digital infrastructure, the understanding among students and teachers regarding the urgency of MBKM and the Kampus Mengajar program remains critically limited. This community service aims to accelerate the understanding of this policy and to institutionalize formal partnerships. The implementation method utilized a participatory-educative approach comprising three stages: analysis of the partner’s literacy paradox, interactive socialization of career opportunities in the Society 5.0 era, and the institutionalization of cooperation (Perjanjian Kerja Sama/PKS). The results indicate a transformation in student understanding. Qualitatively, success indicators were evident in the shift of student discussion substance; moving from skepticism due to financial constraints to competency-based optimism after comprehending the Flagship scholarship schemes. This activity also successfully produced a strategic output in the form of a signed Cooperation Agreement (PKS), which serves as the legal foundation for the school to transform into a social laboratory within the Universitas Pattimura Independent MBKM ecosystem.